2022
DOI: 10.1186/s12872-022-02701-x
|View full text |Cite
|
Sign up to set email alerts
|

Major cardiovascular events after bone marrow mononuclear cell transplantation following acute myocardial infarction: an updated post-BAMI meta-analysis of randomized controlled trials

Abstract: Background The effect of bone marrow-derived mononuclear cells (BM-MNCs) after acute myocardial infarction (AMI) on myocardial function indices such as left ventricular ejection fraction has been widely studied. However, the effect of this intervention on major adverse cardiovascular events (MACE) was not the principal purpose of most investigations and its role is unclear. The aim of this study was to investigate the possible long-term clinical efficacy of BM-MNCs on MACE after AMI. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…A Cochrane meta-analysis showed that treating AMI patients with a reduced LVEF with BM-MNCs effectively increases LVEF, yielding survival and functional benefits in patients below 55 with an EF below 37% [ 33 ]. On the other hand, two more recent meta-analyses found that while post-AMI therapy with BM-MNCs can decrease hospitalization for CHF and re-infarction, their effect on all-cause mortality and stroke rate is questionable [ 29 , 30 ]. Another cell type is MSCs, which were about twice as effective as BM-MNCs in the TAC-HFT trial [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…A Cochrane meta-analysis showed that treating AMI patients with a reduced LVEF with BM-MNCs effectively increases LVEF, yielding survival and functional benefits in patients below 55 with an EF below 37% [ 33 ]. On the other hand, two more recent meta-analyses found that while post-AMI therapy with BM-MNCs can decrease hospitalization for CHF and re-infarction, their effect on all-cause mortality and stroke rate is questionable [ 29 , 30 ]. Another cell type is MSCs, which were about twice as effective as BM-MNCs in the TAC-HFT trial [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…More details about HSCs and MSCs are addressed later in this review. Their abundance and accessibility allow autologous implantation without previous expansion, which prevents stem cell differentiation and immune rejection and promotes cellular migration to the affected tissues [ 20 ]. A recent meta-analysis showed improved myocardial performance after BMMNCs transplantation and reduced rehospitalization and reinfarction rates, although no effect on reduction of cardiovascular-related death was observed [ 21 ].…”
Section: Human Stem Cell Types and Sources For Cvd Research And Treat...mentioning
confidence: 99%
“…However, the BAMI researchers observed the clinical benefit of reduced heart failure associated hospitalization in patients receiving BMNC therapy (45). In a recent meta-analysis study, Attar et al further confirmed that BMNC therapy improved clinical outcomes in terms of reinfarction and hospitalization for heart failure (46). Thus, it is crucial to identify a better cell type, optimal dose, and route of transplantation to strengthen the therapeutic effect and achieve a statistical significance in the post-BAMI era (10).…”
Section: Cell Therapy For Acute Myocardial Infarction In Post-bami Eramentioning
confidence: 99%